2022
DOI: 10.1007/s11199-022-01329-7
|View full text |Cite
|
Sign up to set email alerts
|

“There’s No Sewing Classes, There’s No Bedazzling Seminars”: The Impact of Masculinity on Social Connectedness and Mental Health for Men Living in Inner-Regional Australia

Abstract: Regional Australian masculinities are typified by ‘traditional’ values (e.g., stoicism, self-reliance) known to restrict social connectedness. Thus, these masculinities have been implicated in worsening men’s mental health. What remains unclear, however, is how men living in inner-regional communities (i.e., townships on the fringes of major cities) might uniquely experience masculinity, social connectedness, and mental health. We interviewed 29 boys/men and one non-binary participant ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Indeed, prior qualitative research with Australian men has documented how masculinities and culture can be intertwined in their impact on mental health (Sharp et al, 2023). The mental health of Australian men living in regional communities can also be uniquely impacted by the cultural contexts that permeates regional communities (Bonell et al, 2023). In other cultural contexts outside of Australia, greater endorsement of the traditionally masculine norm of primacy of work has been found to be higher among Asian American relative to Caucasian men (Owen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior qualitative research with Australian men has documented how masculinities and culture can be intertwined in their impact on mental health (Sharp et al, 2023). The mental health of Australian men living in regional communities can also be uniquely impacted by the cultural contexts that permeates regional communities (Bonell et al, 2023). In other cultural contexts outside of Australia, greater endorsement of the traditionally masculine norm of primacy of work has been found to be higher among Asian American relative to Caucasian men (Owen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently identified the role of objective social isolation in increasing male loneliness. In terms of friendship, having fewer friends, lacking close male friendships and having limited opportunities for social interactions have all been associated with increased loneliness [17][18][19][20][21][22][23]. While much of this research has focused on younger men, we may anticipate that poor-quality or lost friendships may also foster loneliness amongst older men.…”
Section: Predictors Of Male Lonelinessmentioning
confidence: 98%
“…In light of these variations, certain predictors of loneliness appear consistent throughout life, such as the quality and quantity of social relationships. Friendship factors, such as having fewer friends, lacking close male friendships and limited opportunities for social interactions have been associated with increased loneliness amongst younger men (13,20,21,22,23,24,25). Romantic relationship factors like the absence of a romantic partner, divorce, or the loss of a partner have been linked to higher levels of loneliness among men (11,15,20,21,26,27,28).…”
Section: Predictors Of Male Lonelinessmentioning
confidence: 99%